2022
DOI: 10.1088/1742-6596/2362/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lateral rotor spacing on the benefits in power generated by multi-rotor configurations

Abstract: In this work, an analysis of the rotor wakes interaction for different array configurations of onshore wind turbines, has been made using CENER’s in-house aerodynamic module, called AeroVIEW. The study focuses on how the distance between rotors affects the increases in power and thrust obtained by configurations with more than one laterally aligned rotor. Two configurations of laterally aligned multi wind turbines of NREL 5-MW type, operating at 8 m/s wind speed and 9.21 rpm, have been analyzed. The first one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Aerodynamic interaction between rotors may be included within BEM aerodynamics by first using CFD‐based models to quantify the steady‐state velocity field around the rotors for different system states, and by later including the resulting wind velocity deficit in the undisturbed velocity field used for analysis. Furthermore, recent work from Martín‐San‐Román et al studied the aerodynamic influence of a two‐rotor system by means of an experimental aerodynamic module based on the free wake vortex method (FVM) 41 . Results indicated that the variation of the mean thrust coefficient compared with a single‐rotor configuration is small (about 2%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerodynamic interaction between rotors may be included within BEM aerodynamics by first using CFD‐based models to quantify the steady‐state velocity field around the rotors for different system states, and by later including the resulting wind velocity deficit in the undisturbed velocity field used for analysis. Furthermore, recent work from Martín‐San‐Román et al studied the aerodynamic influence of a two‐rotor system by means of an experimental aerodynamic module based on the free wake vortex method (FVM) 41 . Results indicated that the variation of the mean thrust coefficient compared with a single‐rotor configuration is small (about 2%).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, recent work from Martín-San-Román et al studied the aerodynamic influence of a tworotor system by means of an experimental aerodynamic module based on the free wake vortex method (FVM). 41 Results indicated that the variation of the mean thrust coefficient compared with a single-rotor configuration is small (about 2%). Moreover, previous work in different fields concerning similar applications, such as the study of thrust imbalance due to aerodynamic interactions in unmanned aerial vehicles (UAVs), also suggests that the effect of aerodynamic interactions on the aerodynamic loads acting on the system may not be significant enough to compromise the results obtained with the method employed in this work.…”
Section: Multi-rotor Wind Turbine System (2wt)mentioning
confidence: 96%
“…Their computational study showed an increase of both power output and thrust force of a multirotor with seven rotors (MR7) compared to a single rotor, and identified local regions of increased flow velocities in the wake between the rotors. The influence of lateral rotor spacing on power and thrust was investigated by Martín San Román et al [4]. Using free-wake vortex methods, they showed increasing power and thrust coefficients when the spacing between the rotors was decreased.…”
Section: Introductionmentioning
confidence: 99%